(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Immortals of Meluha is Amish Tripathi’s first novel from the Shiva Trilogy series. It is set in 1900 BC, in what the modern Indians wrongly call the civilization of the Indus Valley. The inhabitants of that land called it Meluha-a near-perfect kingdom that Lord Ram, one of the greatest monarchs ever lived, built many centuries ago. The storey takes place in Meluha’s imaginary world, and how a tribal leader named Shiva saves them from their wars. This paper discusses about the immortals of meluha the novels of Amish Tripathi.